Respuesta :

Answer:

y = -3x + 1

Step-by-step explanation:

Step 1:  Determine what the values of x1, x2, y1, y2 are

To find the slope use the formula, m = [tex]\frac{y2-y1}{x2-x1}[/tex]

(x1, y1) is (1, -2)

(x2, y2) is (3, -8)

Step 2:  Plug into the slope formula

m = [tex]\frac{y2-y1}{x2-x1}[/tex]

m = [tex]\frac{-8 - (-2)}{3-1}[/tex]

m = [tex]\frac{-8 + 2}{2}[/tex]

m = [tex]\frac{-6}{2}[/tex]

m = -3

Step 3:  Determine what the values of y1, m, x1 in the point slope form

(y - y1) = m(x - x1)

(x1, y1) is (1, -2)

m = -3

Step 4:  Plug into the point slope form

(y - y1) = m(x - x1)

(y - (-2)) = -3(x - 1)

y + 2 - 2 = -3x + 3 - 2

y = -3x + 1

Answer:  y = -3x + 1

Answer:

Step-by-step explanation:

[tex]y-y_{1}=\frac{y_{2}-y_{1}}{x_{2}-x_{1}} (x-x_{1})\\y+2= \frac {-8+2}{3-1} (x-1)\\y+2=-3(x-1)\\or~y=-3x+3-2\\or~y=-3x+1[/tex]